STRATEGI PEMASARAN BUAH LOKAL JAWA TIMUR - Sudiyarto, Sudiyarto (Jurnal Sosial Ekonomi Pertanian, 2011)
This study aims to examine mechanism of the parties involved on reclaiming in acquiring, controlling and maintaining the flow of benefits from protected forest protection and its distribution. The method of research was qualitative approach using case study strategy and multi method. Reclaiming of protected forest by community of coffee growers in Sidomulyo has ideological purpose that is related to the reasons of morality, justice, normative and history. It also has a practical purpose that is related to the economic and ecological value of forests. The main actors in the conflict for agrarian resource (protected forests) are community of coffee growers and Perhutani. In addition there are also other actors are indirectly involved. They are private sector (traders, owners of capital and exporters) and government (village and region). The actors have their own interests to protected forest as conflicted resource. Mechanism of the parties in acquiring, controlling and maintaining the flow of benefits from protected forest and its distribution is influenced by the ability to access the technology, capital, markets, knowledge, authority, social identity and social relations.Keywords: Contestastion, Conflict, Access mechanism, and Agrarian resource.